2020
DOI: 10.1177/0262728019894753
|View full text |Cite
|
Sign up to set email alerts
|

Tribal and Non-Tribal Farmers’ Land Rights and Food Security Promotion in Telangana

Abstract: This article examines and compares the status of land rights and their impacts on agricultural productivity, food security and well-being in a set of tribal and non-tribal villages in Telangana. Based on an intensive field survey, the research confirms that tribals without formal land rights remain largely unable to benefit from government support and access to private institutions in terms of getting credit and farm extension, whereas in non-tribal villages, government organisations are pro-active in providin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Further, the lack of absolute or non-derivative property rights constrains the ability of farming households to invest at the farm level such as to plant cash crops, consequently limiting their income generation potential (Odoemelam et al, 2013;Oluwatayo et al, 2019). Also, Reddy et al (2020) in a similar study found that respondents without formal land rights remain largely unable to benefit from government support and were unable to access credit and farm extension services from private institutions. Therefore, attaining adequate agricultural production and food security is difficult as the population continues to grow and agricultural land becomes scarce, fragmented, and illegally held [Federal Ministry of Agriculture & Rural Development (FMARD), 2016].…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…Further, the lack of absolute or non-derivative property rights constrains the ability of farming households to invest at the farm level such as to plant cash crops, consequently limiting their income generation potential (Odoemelam et al, 2013;Oluwatayo et al, 2019). Also, Reddy et al (2020) in a similar study found that respondents without formal land rights remain largely unable to benefit from government support and were unable to access credit and farm extension services from private institutions. Therefore, attaining adequate agricultural production and food security is difficult as the population continues to grow and agricultural land becomes scarce, fragmented, and illegally held [Federal Ministry of Agriculture & Rural Development (FMARD), 2016].…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…There are 62 different tribes in the state of Odisha. Tribal farmers are mostly engaged in subsistence agriculture in which they produce variety of crops for self-consumption purposes due to their understanding as well as the geographical position (Reddy et al, 2020). The state's agriculture sector engages about 60% of the population in the agriculture sector (Government of Odisha, 2021).…”
Section: Introductionmentioning
confidence: 99%